Waste management of traditional dairy farming for alternative energy: A feasibility study on biogas processing in Dusun Banyudono, Semarang Regency, Indonesia - Ritma Kartika Dewi; Dwi Wahyuningsih; Dwi Elita Sari; Setia Humani Jatiningrum; Widhi Handayani (Center for Science and Technology, IAIN Surakarta, 2021)
Dairy farming's waste contributes to greenhouse (GHG) gas emission, and its conversion into biogas is of potential benefit to reduce emission while providing alternative energy for the dairy farmers. Although biogas conversion has been conducted in Banyudono, Semarang Regency, not all dairy farmers are interested in this biogas processing, and it seems to be related to the question of the benefit they would receive. This research aims to explain the management of the waste of dairy farming in Banyudono and a feasibility study on dairy farming in Banyudono, if biogas processing is not to be included and along with biogas processing. This study combines qualitative and quantitative approaches by conducting interviews, direct observation, documentation, and a feasibility study on biogas processing. This study finds that 8,400 kg of cow manure and 4,950 liters of urine are produced every day, by only 5.76% is processed into biogas, 11.25% is processed into manure, while 82.98% of the waste is left unused. The feasibility study indicates that biogas processing tends to increase the benefit received by independent farmers instead of the member of the dairy farmer group discussed in the study. Furthermore, our study reveals issues regarding the dairy farmers' environmental awareness, poor management of biogas distribution on the farmer group level, and technology adoption problems. Finally, a model of integrated farming system is composed to address the issue of waste management in Banyudono.